Analysis of Light Vehicle Engineering Skill Level on Work Readiness of Student - Supriadi, Supriadi; Haruna, Haruna (Journal of Research and Innovation, 2023)
This study aims to: (1) knowing the description of the skills of students majoring in light vehicle engineering at SMK Muhammadiyah Wonomulyo, (2) knowing the description of the job readiness of students majoring in light vehicle engineering at SMK Muhammadiyah Wonomulyo, totaling 88 people consisting of TKR A and TKR B. The research data was collected by using observation and questionnaire (questionnaire), the data obtained is processed using descriptive statistical analysis. The results showed that the student skills of 88 students obtained 21 students (23.9%) in the very good category, 66 students (75%) in the good category, 1 student (1.1%) in the sufficient category, and none in less category. In the category of student work readiness, 17 students (19.3%) were in the very good category, 60 students (68.2%) were in the good category, 11 students (12.5%) were in the sufficient category, and none were in the good category. less category.